Evaluasi Kinerja Fisik Bangunan Irigasi pada Daerah Irigasi Santren, Desa Jatisari, Kecamatan Tajinan - Winardi Winardi; Kiki Frida Sulistyani; Handika Setya Wijaya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
The agricultural sector relies heavily on the reliability of irrigation infrastructure to ensure food production stability. This study aims to evaluate the physical performance of irrigation infrastructure in the Santren Irrigation District (DI), located in Jatisari Village, Tajinan Subdistrict, Malang Regency. The Santren IR serves 50 hectares of agricultural land supported by a network of primary canals spanning 2,488.45 meters, secondary canals 198.71 meters, and tertiary canals 167.87 meters. The research method employed was quantitative descriptive, involving an inventory of damage through field surveys and visual inspections of structures and canals. Performance assessment was based on the Irrigation System Performance Index (IKSI) criteria in accordance with Ministry of Public Works and Public Housing Regulation No. 12/PRT/M/2015, which covers the physical condition of main structures, conveyance channels, control structures, and other supporting facilities. The research results indicate that the physical infrastructure at the Santren Irrigation District is generally in adequate condition. Based on calculations, the total Irrigation System Performance Index (IKSI) score was 85.29%. This score places the performance of the Santren Irrigation District’s irrigation system in the “Still Functioning Well” category. However, several technical issues were identified in the field, such as minor cracks in the concrete wall structures, corrosion on the water gates, and sediment accumulation in the sediment traps and outflow channels, which have the potential to hinder the smooth distribution of water. Based on these findings, it is recommended that the managing authority (the Public Works and Water Resources Agency of Malang Regency) implement more systematic routine maintenance, particularly sediment dredging in sediment traps and functional repairs to corroded floodgate components. In addition, improvements to the quality of inspection roads are necessary to ensure unimpeded operational access and the sustainable monitoring of the irrigation network.